Working with public contributors in Parkinson's research: What were the changes, benefits and learnings? A critical reflection from the researcher and public contributor perspective - Fiona E. Lithander; Emma Tenison; David Ashford Jones; Sue Stocker; Noreen Hopewell‐Kelly; Andy Gibson; Carmel McGrath (Health Expectations)
Abstract Introduction This paper provides a critical reflection from both the researcher and public contributor (PC) perspective on the benefits and the learnings taken from involving PCs in research related to Parkinson's. Approach to Patient and Public Involvement (PPI) This paper reports on how PCs shaped the design and development of the PRIME‐UK research programme study materials through input into information leaflets, consent forms and other patient‐facing documents used across three studies within the PRIME‐UK research programme. The PRIME‐UK research programme is designed to improve the quality of life of people with Parkinson's and this project included three studies: a cross‐sectional study, a randomised control trial and a qualitative study. We captured these impacts using Public Involvement Impact Logs, which provide a framework allowing researchers and PCs to report on the learnings, immediate outcomes and impacts from PPI. For this project, the impact logs enabled us to provide reflections from PCs and researchers on the process of involving ‘the public’ in Parkinson's research. Findings This paper builds on existing evidence of the range of benefits and challenges that emerge from working with patients and the public in Parkinson's research; this includes reflecting on the changes made to the study materials and benefits for the people involved. Four themes emerged from the reflections that were common to the researchers and PCs; these were the importance of providing a supportive environment; recognition of the benefit of the evaluation of the impact of PPI; acknowledgement that engagement of PPI can make a positive difference to the research process and that timely communication and the use of face‐to‐face communication, where available, is key. Furthermore, we demonstrate how impact logs provide a useful and straightforward tool for evaluating public involvement practices and supporting the feedback process. Conclusion We offer key recommendations for involving patients and the public in Parkinson's research and suggest approaches that could be implemented to capture the impacts of public involvement. Public Contribution Public contributors (PCs) were involved in the design and development of the participant information leaflets, consent forms and other patient‐facing documents used for studies within the PRIME‐UK research programme. In addition, PCs evaluated their involvement using impact logs and co‐authored this paper.